Tracing the Roots of Cognitive Linguistics in Hermann Paul’s “Principles of the History of Language” - Romanova, Tatyana V. V. (Respectus Philologicus, 2015)
The paper examines the impact of Hermann Paul’s ideas on the development of anthropocentric cognitive linguistics in Russia and Europe. The anthropocentric and pragmatic approaches to the study of language, related, in particular, to the consideration of language as “the language of the individual” and a product of personal experience, were formulated by the German linguist Hermann Paul (1846-1921) in his Principles of the History of Language (1920). In this important work, Paul argues that language development is driven by subjective, psychological factors, acknowledging the Man’s central role in the learning process (anthropocentrism). Viewing Paul’s position from the vantage point of modern linguistics, the article seeks to establish the rightness of the cognitive school in linguistics, provides a brief overview of Paul’s key ideas and concludes that he anticipated and formulated the main principles of the cognitive approach to language, namely: language as a product of individual experience, the role of individual notions in forming a word’s meaning, analogy as a mechanism of language acquisition, metaphor as a mechanism of learning and the connection of language with other mental processes.
Keywords: Anthropocentrism; Notion; Understanding; Cognitive Linguistics; Language of an Individual